BANK HAJI INDONESIA : OPTIMALISASI PENGELOLAAN DANA HAJI UNTUK KESEJAHTERAAN JAMA’AH HAJI INDONESIA (SEBUAH GAGASAN) - Riko Nazri (Khazanah: Jurnal Mahasiswa, 2013)
Writing in the scientific article is to give an idea of writing about the idea of established an Islamic finance institution called Bank Haji Indonesia (BHI) as Financial institution that manages funds in full pilgrims collected up to trillions of rupiah each year in the Ministry of Religious Affairs of the Republic of Indonesia. Haji as the five pillars of Islam which was not only aimed at increasing piety and spiritual values of the perpetrators, but also save a great economic potential (Economic Hajj). The number of pilgrims from Indonesia is the most compared to other countries in the world that every year is always to obtain a quota of up to 200 thousand over the congregation. If we analyze each year there are 210-215 candidate hajj with a 16 thousand pilgrims among Hajj plus. If the average is taken every pilgrims issued ONH (regular or plus) of Rp 30 million it will get the Rp 6.45 trillion. From this simple calculation we get spending any pilgrims estimated to average USD 35 million. Up to by July 1, 2011 BPIH initial deposit ranging up to figures collected Rp. 31.34 trillion and the Ummah Endowment Fund of Rp 1.9 trillion. If the pilgrim fund can be managed optimally will certainly have an impact and benefits for the welfare of pilgrims indonesia.